FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA - Gusti Ayu Mahanavami (Forum Manajemen STIMI Handayani Denpasar, 2013)
Banking is everything which is concerning about Bank, including institute,business activity, and also the way of and process to execute its effort, while Bankrepresent the nucleus, core institute from financial system, every state which is theeffort in essence muster the fund from society which is its for in the form of saving,deposit and giro, channelling to society needing fund in the form of credit and alsoservice in payment traffic. .Ability of the banks in gain profit is measured by returnon assets (ROA). The purpose of this research is to examine influence of CapitalAdequacy Ratio (CAR), Non Performing Loan (NPL), Net Interest Margin (NIM),Loan to Deposit Ratio (LDR), and BOPO through Return On Asset (ROA) of publicbanking listed at Indonesian Stok Exchange during 2011-2012.Research using purposive sampling method for taking samples. Data obtained onthe basis of publication Annual Bank, obtained 5 samples of General Bank. Samplesused in this research are public banking listed at Indonesian Stock Exchange onperiod 2011-2012. Analysis technique used is multiple linear regression analysis. The results of this research found that Capital Adequacy Ratio (CAR) andLoan to Deposit Ratio (LDR) hasn’t significant positive effect to Return On Asset(ROA), Non Performing Loan (NPL) hasn’t significant negative effect to ReturnAsset (ROA), Net Interest Margin (NIM) has significant positive effect to Return OnAsset (ROA), and BOPO has significant negative effect to Return On Asset (ROA).